2007
DOI: 10.1111/j.1600-0897.2007.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of T Cells by Cross‐Linking Qa‐2, the Ped Gene Product, Requires Fyn

Abstract: Fyn, PI-3 kinase, and Akt are required for the activation of T cells by cross-linking Qa-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Also, both sDab1 isoforms and sFyn-B were expressed in adipose tissue, and it was shown that the loss of Fyn markedly improved insulin sensitivity[ 34 ], hence, they might interact to influence fatty acid metabolism. The high expression level of sFyn-T in spleen and lung suggests a role in the immune system, as shown in other species; for instance, Fyn is required for the activation of T cells[ 35 ]. Further investigation is needed to explore the multiple roles of sDab1 isoforms in various tissues in addition to the regulation of neuronal migration and neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Also, both sDab1 isoforms and sFyn-B were expressed in adipose tissue, and it was shown that the loss of Fyn markedly improved insulin sensitivity[ 34 ], hence, they might interact to influence fatty acid metabolism. The high expression level of sFyn-T in spleen and lung suggests a role in the immune system, as shown in other species; for instance, Fyn is required for the activation of T cells[ 35 ]. Further investigation is needed to explore the multiple roles of sDab1 isoforms in various tissues in addition to the regulation of neuronal migration and neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Src family kinases (SFKs) has been involved in EMT 28 , 29 and pluripotency 30 , and Qa-2 appears to mediate activation of the SFK member Fyn 31 , we treated 4T1m and 4T1t cell lines with two well-established inhibitors of SFK activity: Dasatinib and PP2 32 . Dasatinib at a concentration of 100 nM had an apparent cytotoxic effect on the cultures, causing a high proportion of cell death in both cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…However, the α3 domain of Qa-2 is unable to interact with CD8 in order to effectively activate cytotoxic T cells (44). Qa-2 has been reported to mediate signal transduction pathways, as antibody-induced crosslinking of Qa-2 promoted proliferation of resting T cells depending on Fyn (a member of the Src family of kinases), PI-3 kinase and Akt (45). Also, Qa-2 is required for the selection of intraepithelial unconventional CD8αα/TCRαβ T cells, which appear to be regulatory cells involved in maintaining intestinal integrity (46).…”
Section: The Murine Non-classical Mhc Complex Qa-2 Its Role In Embrymentioning
confidence: 99%